Hazards analysis reducing the impact of disasters - Pine, John C. 1946- (CRC Press is an imprint of the Taylor & Francis Group, 2015)
The impacts of natural and man-made disasters have been increasing at exponential rates over the past few decades. Our global interconnectedness and the scale of disaster events has grown to the point where catastrophic disasters have regional, national, and even global economic consequences. This volume presents a systematic process of hazards identification, vulnerability determination, and consequence assessment